Developing Academic Writing Learning Module to Improve Writing Skills of Graduate Program Students - Jumira Warlizasusi; Ifnaldi Ifnaldi; Nuzuar Nuzuar; Ahmad Qodri; Henny Septia Utami (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
Academic writing is one of the skills needed by students, especially postgraduate students. However, there were still many writing problems experienced by Islamic Education Management Postgraduate students of IAIN Curup batch 2020. Therefore, it was necessary to develop a learning model for Academic Writing course. This study aims to investigate the development of a learning model in the Academic Writing course. This study used 4D development research model (Define, Design, Develop, and Disseminate). The result of the study shows that the learning model in the Academic Writing course was carried out into these stages: prewriting stage, drafting stage, responding stage, revising stage, and evaluating stage. By carrying out the academic writing course, there were improvements in the writing skills of the postgraduate students. In the prewriting stage, it was observed that the students had already the skills needed to be possessed in the pre-writing stage. Then in the writing stage, the students had possesed skills in processing or analyzing data, and the students also had been able to revise their writings. This research produced a learning module for the Academic Writing course that has been refined from the modules used so far. The contribution of learning academic writing is in the academic writing course which teaches writing systematics, rules for writing, reference management, how to submit articles to nationally reputable journals, paraphrasing. The results of this course can be seen from student articles which have been published in many accredited journals Sinta 3 and Sinta 4.